Physical Activity Behavior in Swiss Secondary School Students: A Segmented Analysis - Marion Gasser; Andrea-Maria Nadenbousch; Fabienne Egger; Mario Kamer; Stefan Valkanover; Mirko Schmidt (Current Issues in Sport Science)
Introduction Physical activity (PA) levels decline from childhood to adolescence, and many Swiss adolescents do not achieve the WHO's recommendation of 60 minutes of daily moderate-to-vigorous physical activity (MVPA) (Bringolf-Isler et al. 2016). To design effective interventions, analyzing adolescents' PA behavior across different daily time segments is essential to better understand which segments offer the greatest potential for improving physical activity levels (Saint-Maurice et al., 2018). As adolescents spend a substantial part of their day in school, it is crucial to focus not only on leisure but also on school time. Therefore, this study examines the segmented PA behavior of Swiss adolescents during specific school and leisure time segments and evaluates their compliance with the respective recommendations.